Two rumen-protected amino acids in dairy cows' feed change the protein content of milk - J Chow; E DePeters; R Baldwin (California Agriculture, 1990)
Including fat in the diet of dairy cows often results in a decrease in the concentrations of total protein and casein in milk. In this study, the addition of rumen-protected methionine and lysine to such a diet increased the total protein and casein contents of milk produced by lactating cows.